1996
DOI: 10.1038/nm0496-449
|View full text |Cite
|
Sign up to set email alerts
|

Human eotaxin is a specific chemoattractant for eosinophil cells and provides a new mechanism to explain tissue eosinophilia

Abstract: Eotaxin is an eosinophil-specific chemoattractant that has been recently identified in rodent models of asthma and host response against tumors. To determine whether a similar molecule might play a role in human inflammatory diseases characterized by eosinophilia, we isolated the human eotaxin gene. We demonstrate that human eotaxin is an early response gene of cytokine-stimulated epithelial and endothelial cells, and is induced in peripheral blood eosinophils by interleukin-3. Eotaxin is directly chemotactic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
407
2
13

Year Published

1998
1998
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 646 publications
(442 citation statements)
references
References 33 publications
20
407
2
13
Order By: Relevance
“…10C). Eotaxin is well recognized as a potent chemoattractant for eosinophils (46,47). Although eosinophil accumulation was not compared in WT versus Tbx21 2/2 mice, it has previously been reported that Ghanian pediatric patients with CM had uniformly low eosinophil counts because of tissue sequestration and destruction rather than decreased production during acute illness followed by eosinophilia 30 d after cure (48).…”
Section: Figurementioning
confidence: 99%
“…10C). Eotaxin is well recognized as a potent chemoattractant for eosinophils (46,47). Although eosinophil accumulation was not compared in WT versus Tbx21 2/2 mice, it has previously been reported that Ghanian pediatric patients with CM had uniformly low eosinophil counts because of tissue sequestration and destruction rather than decreased production during acute illness followed by eosinophilia 30 d after cure (48).…”
Section: Figurementioning
confidence: 99%
“…Tumour infiltrating eosinophils may also modulate angiogenesis and desmoplastic reaction (Ono et al, 1997;Samoszuk, 1997). Eotaxin is the most researched C-C chemokine (Fankin et al, 2000), its human gene has been characterized and shown to be an early response gene of cytokine-stimulated epithelial and endothelial cells (Garcia-Zepeda et al, 1996). It may provide the molecular basis for eosinophil recruitment in certain tumours especially of the gastrointestinal tract.…”
Section: Clinicalmentioning
confidence: 99%
“…Eotaxin/CCL11 is a member of the CC chemokine family that has potent chemotactic activity for eosinophils (15,16), basophils (17), mast cells (18), and Th2-type lymphocytes (19). Eotaxin/ CCL11 protein is up-regulated in a variety of inflammatory diseases possessing an eosinophilic component, such as allergic asthma (20,21), chronic sinusitis (22), and allergic rhinitis (23), and is thought to be a key player in the pathogenesis of these conditions.…”
mentioning
confidence: 99%